EDUKASI PENERAPAN DIGITALISASI EKONOMI DALAM UPAYA MENINGKATKAN PRODUKTIVITAS UMKM DI WILAYAH KELURAHAN CAWANGJAKARTA TIMUR PADA MASA SETELAH PANDEMI COVID-19 - Riwandari Juniasti Purnama; Fery Tobing; Edison Siregar; Julita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
This Community Service aims to provide understanding to MSMEs in the Cawang area regarding the application of economic digitalization to increase the productivity of MSMEs in the region, in particular providing an understanding of QRIS (Quick Response Code Indonesian Standard). It is hoped that these MSMEs will accept payments from their customers through QRIS so that they do not rely on cash payments only. The approach taken is to provide education about the benefits of using QRIS and how to activate it. Regarding payment transactions that are often made, 70% stated that they received payments in cash, meaning that more than half of the participants had not received QRIS. Regarding QRIS, 55% of participants stated that they had heard of it, but 54% stated that they were unfamiliar with it or not at all familiar with it. 72% want to expand payment methods so that they don't only accept cash but also non-cash. 77% said they were interested in knowing more about QRIS, and 72% said they were interested in trying QRIS. After education, participants who are interested in receiving payments with QRIS are directed to activate. Keywords: education, QRIS, UMKM, digitalization.